2019
DOI: 10.5194/os-15-1761-2019
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear aspects of the tidal dynamics in the Sylt-Rømø Bight, south-eastern North Sea

Abstract: Abstract. This study is dedicated to the tidal dynamics in the Sylt-Rømø Bight with a focus on the non-linear processes. The FESOM-C model was used as the numerical tool, which works with triangular, rectangular or mixed grids and is equipped with a wetting/drying option. As the model's success at resolving currents largely depends on the quality of the bathymetric data, we have created a new bathymetric map for an area based on recent studies of Lister Deep, Lister Ley, Højer Deep and Rømø Deep. This new bath… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
(72 reference statements)
0
16
0
Order By: Relevance
“…Previous work has demonstrated that the model can accurately reproduce tidal dynamics ( [25][26][27]). To test how the current model setup performs at reproducing the main tidal harmonics in long-term simulations, we analyzed observed sea-level height at several regional stations by extracting the amplitudes and phase of nine harmonics for comparison with model results.…”
Section: Tidal Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that the model can accurately reproduce tidal dynamics ( [25][26][27]). To test how the current model setup performs at reproducing the main tidal harmonics in long-term simulations, we analyzed observed sea-level height at several regional stations by extracting the amplitudes and phase of nine harmonics for comparison with model results.…”
Section: Tidal Dynamicsmentioning
confidence: 99%
“…Here, we present the results of simulations performed with the newly developed FESOM-C model [25,26]. FESOM-C is a coastal branch of The Finite-volumE Sea ice-Ocean Model (FESOM2) [1].…”
Section: Introductionmentioning
confidence: 99%
“…FESOM-C is a coastal branch of the global Finite volumE Sea ice Ocean Model (FESOM2) (Danilov et al, 2017;Androsov et al, 2019;Kuznetsov et al, 2020;Fofonova et al, 2019). FESOM-C solves 3-D primitive equations in the Boussinesq, hydrostatic and traditional approximations for the momentum, continuity, and density constituents, and uses a terrain-following coordinate in the vertical.…”
Section: Fesom-cmentioning
confidence: 99%
“…Juznetsov et al [7] presented the results with a new 3D unstructured mesh finite volume coastal model, FESOM-C [12]. Over existing structured mesh models, FESOM-C with hybrid meshes (quadrilaterals and triangles) is geometrically flexible and allows the resolution of the mesh to be varied (within reasonable limits) in both the horizontal and vertical, letting the mesh contour complex coastlines.…”
Section: Author Contributionsmentioning
confidence: 99%